Characteristics of tornado wind loads and examinations of tornado wind load provisions in ASCE 7–16. (15th August 2021) - Wang, Jin; Cao, Shuyang
Highlights: The aerodynamics of a cubic building subjected to tornado vortices were studied. Tornado can produce more negative pressures on roof and leeward walls. ASCE 7-16 underestimates the uplift by 20% for building with dominant opening. ASCE 7-16 significantly underestimates the tornado wind loads on walls. Abstract: This paper aims to study the characteristics of tornado-induced wind loads over smooth and rough ground and subsequently examine the tornado wind load provisions in ASCE 7–16. The pressure measurement on a cubic building subjected to stationary tornado vortices was conducted in the tornado simulator at Tongji University, China. The overall uplift and base shear for MWFRS and wind loads for Components & Cladding are analyzed to assess the newly proposed tornado wind load provisions. The results indicate that the simulated tornado vortices with swirl ratio of 0.72 can represent the EF3 Spencer tornado vortices. In addition, the external building surfaces are significantly affected by the terrain when they are immersed below 3 to 5 times the roughness element height. Tornado would induce more intense aerodynamic loads on roof, leeward wall and side wall than those from conventional boundary-layer winds. The Extended method by amplifying the gust effect factor to 0.9 and the Simplified method by introducing a tornado factor in ASCE 7–16 are able to conservatively evaluate the overall uplift and base shear on the building without dominant openings. However, these two approaches would significantly underestimate the overall uplift on building with a dominant opening as much as 21% and 22%, respectively. The underestimation of peak negative force on the edge zone of wall can reach 39% 48% using Extended method.